Overview of Early Warning Alert Respone System (EWARS) Performance at Trenggalek District in 2016 - melisa putri anggraini (Universitas Airlangga, 2017)
ABSTRACT EWARS implementation in Trenggalek has applied since 2013. EWARS was rated from accuracy and completeness of report. Accuracy and completeness of report is the indicator to determine public health center (PHC) performance on the EWARS implementation. The objective of this research is to analyze EWARS performance of PHC in the health office on 2016 with reviewing the accuracy and completeness of report. This research was observational research, that used evaluative design. The subject of this research is surveilance system of EWARS in Health Office of Trenggalek with informant or data resources is EWARS holder in 22 PHC and health Offce. The technique of data collection used primary data and secondary data with questionnaire and observation sheet as instruments. The technique of data processing and analyzing was descriptive. The results of this research showed accuracy of report in Trenggalek on 2016 shows an average of 79%, meanwhile completeness of report in Trenggalek on 2016 of 98,5%. The conclusion of this research was EWARS performance in the PHC seen from accuracy of report showed result that not well yet because accuracy of report that not reached yet the target of 80%, meanwhile based on the completeness of report showed that EWARS performance of PHC already good because has reached the target of 90%. Accuracy and completeness affected by characteristics of the EWARS officer. Therefore need to evaluate on officer who aged 26-45 years old, on the woman officer and officer that has work period ≥2 years. Keywords : Early Warning Alert Response System, outbreak, accuracy and completeness's report, PHC performance